Pulmonary Vein Isolation Using the Visually Guided Laser Balloon: Results of the U.S. Feasibility Study. (10th August 2015) - DUKKIPATI, SRINIVAS R.; WOOLLETT, IAN; McELDERRY, H. THOMAS; BÖHMER, MARIE‐CHRISTINE; DOSHI, SHEPHAL K.; GERSTENFELD, EDWARD P.; HORTON, RODNEY; D'AVILA, ANDRE; HAINES, DAVID E.; VALDERRABANO, MIGUEL; MANGRUM, J. MICHAEL; RUSKIN, JEREMY N.; et al.
Visually Guided PV Isolation Introduction Visually guided laser balloon (VGLB) ablation is unique in that the operator delivers ablative energy under direct visual guidance. In this multicenter study, we sought to determine the feasibility, efficacy, and safety of performing pulmonary vein isolation (PVI) using this VGLB. Methods Patients with symptomatic, drug‐refractory paroxysmal atrial fibrillation (AF) underwent PVI using the VGLB with the majority of operators conducting their first‐ever clinical VGLB cases. The primary effectiveness endpoint was defined as freedom from treatment failure that included: Occurrence of symptomatic AF episodes ≥1 minutes beyond the 90‐day blanking, the inability to isolate 1 superior and 2 total PVs, occurrence of left atrial flutter or atrial tachycardia, or left atrial ablation/surgery during follow‐up. Results A total of 86 patients (mean age 56 ± 10 years, 67% male) were treated with the VGLB at 10 US centers. Mean fluoroscopy, ablation, and procedure times were 39.8 ± 24.3 minutes, 205.2 ± 61.7 minutes, and 253.5 ± 71.3 minutes, respectively. Acute PVI was achieved in 314/323 (97.2%) of targeted PVs. Of 84 patients completing follow‐up, the primary effectiveness endpoint was achieved in 50 (60%) patients. Freedom from symptomatic or asymptomatic AF was 61%. The primary adverse event rate was 16.3% (8.1% pericarditis, phrenic nerve injury 5.8%, and cardiac tamponade 3.5%). There were no cerebrovascular events, atrioesophageal fistulas, or significant PV stenosis. Conclusions This multicenter study of operators in the early stage of the learning curve demonstrates that PVI can be achieved with the VGLB with a reasonable safety profile and an efficacy similar to radiofrequency ablation.